Glucocorticosteroid-induced complications in patients with idiopathic thrombocytopenic purpura - S. G. Zakharov; T. A. Mitina; A. V. Zakharova; R. V. Vardanyan; E. V. Kataeva; Yu. B. Chernykh; L. L. Vysotskaya; L. V. Ivanitskiy; I. N. Kontievskiy; O. P. Madzyara; O. R. Zhuravlev; N. V. Gorgun; et al. (Онкогематология)
Glucocorticosteroids (GCS) are the first-line treatment for idiopathic thrombocytopenic purpura (ITP). Despite their high efficacy in patients with newly diagnosed ITP, an adequate level of platelets remains after GCS withdrawal in only less than 20 % of patients. Additionally, GCS use is associated with an increased risk of different adverse reactions, including serious and life-threatening ones. Thrombopoietin receptor agonists represent a relatively new class of drugs for treating ITP as a second-line therapy. This paper reviews the risks of GCS pharmacotherapy, as well as the evidence supporting the use of thrombopoietin receptor agonists as both first-line and second-line treatment for patients with ITP.